2010
DOI: 10.3892/etm.2010.178
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and biological analysis of active free and conjugated bile acids in animal bile using HPLC-ELSD and MTT methods

Abstract: Abstract. the aim of the present study was to determine the chemical composition and in vitro cytotoxic activity of seven bile samples and bile acids using the high-performance liquid chromatography (hplc)-evaporative light scattering detector (ElSd) method. Free and conjugated bile acid standards were used to identify and quantify the chemical components of the seven animal bile samples. the mtt assay was used to determine the cytotoxic effect of the animal bile samples and the free and conjugated bile acids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…Conjugated bile acids were determined by HPLC-DAD and TUDCA was injected as standard marker to evaluate the quality of BB sample. The result showed that TUDCA was the most abundant component in BB and the yield of TUDCA in BB was 7.84%, which was consistent with our previous report [3]. …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Conjugated bile acids were determined by HPLC-DAD and TUDCA was injected as standard marker to evaluate the quality of BB sample. The result showed that TUDCA was the most abundant component in BB and the yield of TUDCA in BB was 7.84%, which was consistent with our previous report [3]. …”
Section: Resultssupporting
confidence: 92%
“…These include bile from other animals, derivatives from plants, chemical compounds, and synthetic bear bile. Recently, our research provides evidence that bear bile can be easily replaced by those of other animals for certain situations [3]. Despite being an effective option, the sacrifice of animals is frowned upon by animal rights activist.…”
Section: Introductionmentioning
confidence: 99%
“…During past decades, extensive research has been performed to qualify and quantify the composition of bear bile, especially the total and individual bile acids. Modern chemical research indicated that bear bile was composed primarily of bile acids, phospholipids, cholesterol, bile pigments, proteins, and inorganic salts [ 19 ]. Among these components, bile acids may play a major role in therapeutic action for bear bile.…”
Section: Recent Research Progress In Bear Bilementioning
confidence: 99%
“…The average concentrations of TUDCA, TCDCA, and TCA in 93 Ursidae bile salts were 3087.8 ± 1626 μ g/mL, 1968 ± 678.1 μ g/mL, and 212.6 ± 154.1 μ g/mL, respectively [ 21 ]. Of note, it is believed that the relative high level of TUDCA and TCDCA makes bear bile different from biles derived from other animals [ 4 , 15 , 19 ].…”
Section: Recent Research Progress In Bear Bilementioning
confidence: 99%
“…The other studies expressed that bear bile contained ursodeoxycholic acid (UDCA) (Bachrach and Hofmann, 1982). UDCA is relatively low content in bear bile and can't be detected by chromatography (Qiao et al, 2011;Wang et al, 2011). UDCA has been used in the treatment of gallbladder stones as an alternative to cholecystectomy (Tint, 1982).…”
Section: Introductionmentioning
confidence: 99%